PSF e ODM: a influência do Programa Saúde da Família para os estados brasileiros atingirem a meta de mortalidade na infância dos objetivos de desenvolvimento do milênio - Pedro, Márcio Vinícius (Universidade Federal de São Carlos, 2014)
What influence Family Health Program‟ (in portuguese, Programa Saúde da Família, or PSF) had on Brazilian states in their attempt to achieve the Millennium Development Goals - especially on reducing infant mortality until 2015? In 2000, the United Nations along with global leaders established an international research agenda with eight Millennium Development Goals, intending to promote human dignity. The purpose of the present thesis is to evaluate the influence of the Family Health Program - the main strategy to reformulate the basic care - in reducing child mortality within Brazilian states. For this matter, I analyze descriptive and inferential statistics, with bi and multivariate techniques, and data from DATASUS, IBGE and SIGO databases. The present thesis covers the period from 2000 to 2011, when Brazil reached the goal. Throughout this time ten states went above the goal specified by ODM (1,79): in all of them the Program had low range. However, the states with higher PSF range presented higher average rates of reduction of infant mortality. Overall, the hypothesis that PSF has a positive influence on reducing infant mortality rate can be confirmed, considering that the states with higher reduction of the rate had a higher proportion of population benefiting from the PSF.
Keywords: Programa Saúde da Família; Mortalidade infantil; Políticas públicas; Objetivos de desenvolvimento do milênio; Family health program; Infant mortality; Millennium development goals; CIENCIAS HUMANAS::CIENCIA POLITICA